Fatty Acid Profile, Physicochemical Composition, and Sensory Properties of Atlantic Salmon Fish (Salmo salar) during Different Culinary Treatments - Nidelle Sausten Fomena Temgoua; Zongbao Sun; Charles Obinwanne Okoye; Haodong Pan (Journal of Food Quality)
This study was conducted to assess the effects of boiling, steaming, and oven-cooking on the fatty acid profile, physicochemical composition, and sensory properties of Atlantic salmon fish. The protein content of steamed (18.90%) and oven-cooked (20.59%) salmon was significantly higher than that of boiled (16.69%) and raw fish (14.73%). Analysis of the fatty acids profile revealed that steaming significantly (p<0.05) influenced the fatty acid contents of Atlantic salmon by recording the lowest SFA and the highest omega-3, omega-6, and PUFA contents. Textural properties such as hardness, gumminess, and chewiness were significantly higher (p<0.05) in oven-cooked salmon, with steamed salmon having significantly lower and higher values of hardness (75.32 ± 4.73) and springiness (90.56 ± 3.94), respectively. Also, volatile organic compounds, including aldehydes, ketones, and alcohol, were significantly higher (p<0.05) in oven-cooked and steamed salmon. Additionally, the E-nose sensors analysis showed that S2 and S7 were significantly correlated during oven-cooking and steaming. Furthermore, low-field NMR analysis showed that the values of T21 and T22 relaxation characteristics of raw and cooked samples fluctuated, with steamed salmon having the highest peak values indicating reduced proton mobility and increased freedom of the protons compared to other treatments. Therefore, steaming resulted in the best quality salmon when considering the fatty acid profile, physicochemical composition, and sensory properties of Atlantic salmon fish, suggesting further studies to ascertain its effectiveness compared to modern treatments.